THE EFFECT OF TACIT KNOWLEDGE SHARING ON KNOWLEDGE QUALITY TO IMPROVE EMPLOYEE EFFECTIVENESS IN A PUBLIC SERVICE ORGANIZATION - Ononye, Uzoma Heman (LPPM Universitas Malikussaleh, 2025)
This study aimed to examine how tacit knowledge sharing directly and indirectly affects employee effectiveness in a public sector organization, focusing on the role of knowledge quality as a mediating factor. Empirical studies on the outcomes of tacit knowledge sharing remain limited, especially in a public sector organizational context. This cross-sectional study involved obtaining data from 145 healthcare professionals working in the Delta State Ministry of Health in Nigeria and subjecting this data to analysis using the partial least square method. The study found that tacit knowledge sharing and knowledge quality effects on employee effectiveness were positive and significant. Furthermore, knowledge quality mediated the significant and positive effect of tacit knowledge sharing on employee effectiveness. The study concluded that enhancing knowledge quality can achieve an optimal relationship between tacit knowledge sharing and employee effectiveness.